Linear-after-the-exponential (LATE)-PCR: Improved asymmetric PCR for quantitative DNA-analysis. (December 2015) - Schulze Johann, K.; Schürenkamp, M.; Sibbing, U.; Lischka, C.; Pfeiffer, H.; Vennemann, M.
Abstract: Linear-after-the-exponential (LATE)-PCR describes a novel approach to asymmetric PCR which uses adjusted melting temperatures of the limited primer to increase PCR efficiency. In this proof-of-principle study we show that linear amplification is possible over a wide range of amplification cycles. The curve characteristics of the real time PCR show that the plateau effect of conventional PCR can be avoided by this innovative technique.